The Role of Students’ Listening Habits to English Songs in Vocabulary Mastery: A Systematic Literature Review - Muaviyah, Tsalis Aviatun; Yuswandari, Kurnia Devi; Novitaningrum, Angella; Mas'ud, Mohammad; Nahidin, khittotun (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
The rapid growth of digital technology has expanded students’ exposure to English beyond formal classroom settings, particularly through informal activities such as listening to English songs. This study aims to systematically review existing research on students’ listening habits to English songs and their implications for vocabulary mastery in English as a Foreign Language (EFL) contexts. A Systematic Literature Review (SLR) method was employed by analyzing peer-reviewed journal articles published between 2020 and 2025. The selected studies focused on English songs, listening activities, listening habits, and vocabulary learning across various educational levels, ranging from elementary school to university. The reviewed articles were analyzed using thematic synthesis, and key findings were organized into a review table to identify recurring patterns and themes. The results indicate that English songs contribute positively to vocabulary mastery by providing repeated and contextualized exposure to lexical items. The findings also reveal that listening habits to English songs support vocabulary development more effectively when accompanied by active engagement, such as attention to lyrics and word meanings. In addition, English songs enhance motivation, listening comprehension, and pronunciation awareness, which indirectly strengthen vocabulary acquisition. Overall, this review concludes that English songs are an effective and accessible learning resource for vocabulary development in EFL contexts, particularly when listening activities are conducted purposefully rather than passively.